2013
DOI: 10.1101/gad.215533.113
|View full text |Cite
|
Sign up to set email alerts
|

Human ALKBH7 is required for alkylation and oxidation-induced programmed necrosis

Abstract: Programmed necrosis has emerged as a crucial modulator of cell death in response to several forms of cellular stress. In one form of programmed necrotic cell death, induced by cytotoxic alkylating agents, hyperactivation of poly-ADP-ribose polymerase (PARP) leads to cellular NAD and ATP depletion, mitochondrial dysfunction, reactive oxygen species formation, and ensuing cell death. Here, we show that the protein encoded by the human AlkB homolog 7 (ALKBH7 ) gene plays a pivotal role in DNA-damaging agent-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 65 publications
1
64
0
1
Order By: Relevance
“…These include FTO (ALKBH9) that is implicated together with ALKBH5 in the oxidative removal of several modifications including 6‐methyladenosine (m 6 A) from RNA and ALKBH8 that is involved in the generation of 5‐methoxycarbonylmethyluridine (mcm 5 U) in cytoplasmic tRNAs (Fu et al , 2010a,b; Songe‐Møller et al , 2010; Jia et al , 2011; Thalhammer et al , 2011; Berulava et al , 2013; Zheng et al , 2013). So far, only ALKBH7, which was suggested to act on protein substrates during necrosis (Fu et al , 2013; Solberg et al , 2013; Wang et al , 2014), and ALKBH1/ABH1 have been reported to localise to mitochondria; however, the cellular localisation of ABH1 has been a matter of debate (Pan et al , 2008; Westbye et al , 2008; Ougland et al , 2012). We therefore analysed the cellular localisation of ABH1 in HEK293 cells by immunofluorescence analysis and co‐staining with a mitotracker (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…These include FTO (ALKBH9) that is implicated together with ALKBH5 in the oxidative removal of several modifications including 6‐methyladenosine (m 6 A) from RNA and ALKBH8 that is involved in the generation of 5‐methoxycarbonylmethyluridine (mcm 5 U) in cytoplasmic tRNAs (Fu et al , 2010a,b; Songe‐Møller et al , 2010; Jia et al , 2011; Thalhammer et al , 2011; Berulava et al , 2013; Zheng et al , 2013). So far, only ALKBH7, which was suggested to act on protein substrates during necrosis (Fu et al , 2013; Solberg et al , 2013; Wang et al , 2014), and ALKBH1/ABH1 have been reported to localise to mitochondria; however, the cellular localisation of ABH1 has been a matter of debate (Pan et al , 2008; Westbye et al , 2008; Ougland et al , 2012). We therefore analysed the cellular localisation of ABH1 in HEK293 cells by immunofluorescence analysis and co‐staining with a mitotracker (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Since many anti-cancer drugs are inducers of apoptosis, inducing RIP3-dependent necrosis is an attractive strategy to circumvent apoptosis resistance of cancer cells. In addition to DNA alkylating agents, which induce necrosis in the PARP-dependent manner (Zong et al 2004;Fu et al 2013;Sosna et al 2013), some drugs were reported to induce RIP3-dependent necrosis in certain conditions (Tenev et al 2011;Bray et al 2012;Basit et al 2013). Because necrosis also facilitates inflammation, its effect on inflammation in the tumor microenvironment has to be carefully considered (Mantovani et al 2008).…”
Section: Potential Role Of Rip3 In Cancermentioning
confidence: 99%
“…The human AlkB family comprises nine members: ALKBH1-8 and FTO; the family is named after their Escherichia coli ortholog, AlkB (20 (24,25); ALKBH4 regulates the demethylation of actin (26); ALKBH7 is involved with the programmed cell necrosis, although a nucleic acid demethylase activity for it has yet to be reported (27); ALKBH8 was demonstrated to hydroxylate 5-methoxycarbonylmethyluridine in tRNA (28); and FTO prefers both m 3 T ssDNA and m 6 A ssRNA (9,29). ALKBH5 is reported to catalyze N-demethylation of m 6 A ssRNA or ssDNA, but not other tested modified nucleotides (8,30).…”
mentioning
confidence: 99%